Restoration technologies of damaged paddy in hilly post-mining and subsidence-stable areas of Southwest China - Zhong, Shouqin; Wei, Chaofu; Liu, Bo; Zhang, Weihua; Du, Jing; Zhang, Shichao (International Journal of Agricultural and Biological Engineering, 2015)
The paddy fields and water storage facilities are seriously damaged by the coal mine subsiding in the hilly post-mining and subsidence-stable areas in China, which make the farmers there being suffered greatly from the lack of water for traditional rice cultivation and daily life. The purpose of this paper is to find a method to restore the damaged paddy fields, thereby promoting sustainable development of land resources, and alleviating the contradiction between people and land, as well as creating a more inhabitable environment. The research methodology included field experiments, cultivated observation, and field investigation. This paper selected the Songzao Mining Area as the research area, and focused on the restoration technologies of damaged paddy fields, through the following four different measures at three experimental fields: (1) Traditional repeated cattle plowing (CK); (2) Water retention agent with repeated cattle plowing (W&C); (3) Film without holes under tilth depth (FO); and (4) Film with holes under tilth depth (FW). At last, a contrastive analysis of the four measures was made according to the results of the experiments. The results show that the use of water retaining agent with repeated cattle plowing (W&C) can be the most appropriate method to restore the damaged paddy field in the hilly post-mining and subsidence-stable area in southwest China. Compared with the other three measures, its water productivity is the maximum (0.81 kg/m3), and the net income is the highest (1 403 /hm2). What’s more, it is simple, short time-consuming, and low cost, which is benefit to generalize the use of this restoration technology. Keywords: land restoration, damaged paddy field, post-mining and subsidence-stable area, water consumption, hilly areas DOI: 10.3965/j.ijabe.20150802.1467